Предмет: Математика, автор: lilya2901

Пожалуйстааааа помогите.​

Приложения:

Ответы

Автор ответа: greatestgenius
1

Пошаговое объяснение:

\tt\displaystyle \frac{\frac{x}{2}+\frac{3}{4}}{\frac{x}{4}+\frac{3}{2}}=\frac{\frac{5}{2}-\frac{7}{4}}{\frac{7}{2}-\frac{5}{4}}\\\\\\\frac{\frac{2x}{4}+\frac{3}{4}}{\frac{x}{4}+\frac{6}{4}}=\frac{\frac{10}{4}-\frac{7}{4}}{\frac{14}{4}-\frac{5}{4}}\\\\\\\frac{\frac{2x+3}{4}}{\frac{x+6}{4}}=\frac{\frac{3}{4}}{\frac{9}{4}}\\\\\\\frac{2x+3}{4}*\frac{4}{x+6}=\frac{3}{4}*\frac{4}{9}\\\\\frac{2x+3}{x+6}=\frac{1}{3}\\\\(2x+3)*3=(x+6)*1\\\\6x+9=x+6\\\\6x-x=6-9\\\\5x=-3\\\\x=-\frac{3}{5}

Похожие вопросы
Предмет: Английский язык, автор: oksanaslyvar05